Chapter Introduction: Introduction to Medieval and Early Modern Experiences of Gender and Faith - Katajala-Peltomaa, Sari (Taylor & Francis, 2020)
This study is an exploration of lived religion and gender across the Reformation, from the fourteenth to the eighteenth centuries. Combining conceptual development with empirical history, the authors explore these two topics via themes of power, agency, work, family, sainthood, and witchcraft.